2001
DOI: 10.1210/edrv.22.5.0441
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Thyroiditis and Autoimmune Thyroiditis in Women of Childbearing Age: Recent Insights and Consequences for Antenatal and Postnatal Care

Abstract: Postpartum thyroiditis is a syndrome of transient or permanent thyroid dysfunction occurring in the first year after delivery and based on an autoimmune inflammation of the thyroid. The prevalence ranges from 5-7%. We discuss the role of antibodies (especially thyroid peroxidase antibodies), complement, activated T cells, and apoptosis in the outbreak of postpartum thyroiditis. Postpartum thyroiditis is conceptualized as an acute phase of autoimmune thyroid destruction in the context of an existing and ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
130
1
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(151 citation statements)
references
References 253 publications
(256 reference statements)
6
130
1
14
Order By: Relevance
“…Such exposure to allogeneic proteins may represent the link between autoimmunity and genetic polymorphisms, as described in post-transfusion purpura [13]. Other autoimmune diseases favoring this hypothesis and displaying a sex bias are postpartum thyroiditis [14], systemic lupus erythematosus [15] and peripartum cardiomyopathy [16]. Nevertheless, women without pregnancies, men, and children are also likely to be exposed to alloantigens, as maternal cells also traffic into the fetal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Such exposure to allogeneic proteins may represent the link between autoimmunity and genetic polymorphisms, as described in post-transfusion purpura [13]. Other autoimmune diseases favoring this hypothesis and displaying a sex bias are postpartum thyroiditis [14], systemic lupus erythematosus [15] and peripartum cardiomyopathy [16]. Nevertheless, women without pregnancies, men, and children are also likely to be exposed to alloantigens, as maternal cells also traffic into the fetal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…What proportion of maternal hypothyroxinemia during pregnancy can be attributed to elevated TPO autoantibodies (TPOaAbs), for instance, has not been established, nor whether elevated TPOaAbs necessarily reduce thyroxine availability to the developing fetal brain. Nonetheless, several studies of pregnant women with elevated TPOaAbs found that their children had impaired intellectual performance whether or not the mothers also had experienced clinical thyroid dysfunction (11)(12)(13). Investigators from one study reported that children of women with elevated TPOaAbs but normal thyroid function during late gestation scored 10.5 points lower on the McCarthy scale (a proxy for IQ) than those born to women who were TPOaAb-negative (13).…”
mentioning
confidence: 99%
“…At present TPOAb is generally recommended as an useful prognostic factor for development of PPTD [5][6][7][8][9] and particularly fi rst-trimester TPOAb titers showing positive predictive value in assessing the risk of postpartum thyroid disorders. 10 In our study the presence of TPOAb in early pregnancy proved to be a signifi cant prognostic factor for the occurrence of PPTD.…”
Section: Resultsmentioning
confidence: 99%